Coping Strategy on Recidivism Prisoners in Penitentiary Class II B of Garut, West Jawa Indonesia - Agustin, Yulian Mutiara; Hidayati, Nur Oktavia; Shalahuddin, Iwan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Coping strategy is an activity when an individual tries to manage or maintain a distance between existing demands and the resources of his empowers in dealing with stress, recidivism is a crime committed by individuals repeatedly. Recidivism can be avoided if individuals have adequate coping strategy and high self control. This study is aimed to recognize the description of coping strategy for recidivism criminals at a correctional facility in Garut. The research method used was descriptive quantitative, the total sample of this study was 84 respondents gained by total sampling technique. Data collection was obtained through questionnaires from the use of A-COPE coping strategy, measurement, this study used frequency distribution analysis, the result shows that most recidivism criminals as much as 60.7 percent used problem-focused coping strategy  and some respondents as much as 33 people or 39.3 percent used emotion-focused coping strategy, the efforts used are confrontational as much as 59.3 percent. It can be concluded that criminals were mostly more likely to use problem-focused coping strategy as much as 60.7 percent, it is advised that correctional facility class II B Garut provide individual counseling services for recidivism criminals in prison.ABSTRAKStrategi koping ialah peristiwa ketika individu berusaha mengelola atau menjaga jarak antara tuntutan-tuntutan yang ada dengan sumber daya yang ia miliki dalam menghadapi stres, residivisme adalah tindak kejahatan yang di lakukan individu secara berulang. Residivisme dapat di hindari apabila individu memiliki strategi koping yang adekuat serta self control yang tinggi. Tujuan penelitian ini adalah untuk melihat gambaran strategi koping pada narapidana residivis di lembaga pemasyarakatan klas II B Garut. Penelitian ini merupakan penelitian deskriptif kuantitatif, penelitian ini menggunakan teknik total sampling, dengan jumlah sampel sebanyak 84 responden. Pengumpulan data menggunakan kusioner pengukur penggunaan strategi koping A-COPE, Penelitian ini menggunakan analisis distribusi frekuensi, hasil penelitian narapidana residivisme, sebagian besar menggunakan strategi koping yang berfokus pada masalah sebanyak 60,7 persen dan hampir sebagian responden menggunakan strategi koping yang berfokus  pada emosi sebanyak 33 orang atau 39,3 persen, upaya yang di gunakan ialah konfrontatif sebanyak 59,3 persen. Kesimpulan penelitian ini bahwa narapidana sebagian besar lebih cenderung menggunakan strategi koping yang berfokus pada masalah sebanyak 60,7 persen, di saran pada lembaga pemasyarakatan klas II B Garut untuk menyediakan layanan konseling individu bagi narapidana residivisme di Lapas.